2017
DOI: 10.1136/bmjopen-2016-015477
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a realist review of complex interventions to prevent adolescents from engaging in multiple risk behaviours

Abstract: ObjectivesAdolescent risk behaviours are a key health concern. The purpose of this research is to gaina deeper understanding of how, why, for whom, and inwhat circumstances complex adolescent risk behaviourprevention programmes are most successful.Methods and analysisTo understand how adolescent risk behaviour prevention programmes work in a reallife context, a realist synthesis will be undertaken, operationalised in four phases. Phase one Developing a framework to map the theoretical and conceptual landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…Realism is a methodological paradigm that sits between positivism (the world is real and can be observed directly) and constructivism (given that all we know has been processed through the human mind, we can never be sure exactly what reality is). 26 It is flexible to changes and embedded in a social reality that influences how a programme is implemented and how various actors in that reality respond to it. 21 Programmes like the MDS will always rely on human agency to affect change.…”
Section: Methodsmentioning
confidence: 99%
“…Realism is a methodological paradigm that sits between positivism (the world is real and can be observed directly) and constructivism (given that all we know has been processed through the human mind, we can never be sure exactly what reality is). 26 It is flexible to changes and embedded in a social reality that influences how a programme is implemented and how various actors in that reality respond to it. 21 Programmes like the MDS will always rely on human agency to affect change.…”
Section: Methodsmentioning
confidence: 99%
“…A key feature of realist systematic reviews is the input of stakeholders throughout the review to support theory generation, knowledge translation, and impact [1,58]. Cooper and colleagues [61] used this combination of primary (stakeholder input) and secondary (literature searching and synthesis) data in their review of complex interventions to prevent adolescents from engaging in multiple risk behaviours. They argued that the incorporation of primary data in their review gave greater insights into causal factors that might not be identified within the literature and, importantly, provided opportunities for adolescents to have a strong voice in theory development.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence was coded deductively (to help evaluate potential propositions, and draw logical conclusions from emerging patterns in the literature), inductively (enabling new ideas and propositions to emerge from the evidence) and retroductively (identifying and exploring new patterns using theory to offer causal explanation). 32 Forty-nine papers were reviewed in total, of which 29 were accepted for inclusion, 13 papers were rejected as they did not go beyond superficial description or did not introduce any new theory areas that had already been developed and refined in the existing configurations. Where papers reported one study, these were grouped together into one set .…”
Section: Data Extraction and Analysismentioning
confidence: 99%